Tgfbr2 in Dental Pulp Cells Guides Neurite Outgrowth in Developing Teeth - Stanwick, Monica; Barkley, Courtney; Serra, Rosa; Kruggel, Andrew; Webb, Amy; Zhao, Yue; Pietrzak, Maciej; Ashman, Chandler; Staats, Allie; Shahid, Shifa; Peters, Sarah B. (Frontiers in Cell and Developmental Biology, 2022)
Transforming growth factor beta (TGFbeta) plays an important role in tooth morphogenesis and mineralization. During postnatal development, the dental pulp (DP) mesenchyme secretes neurotrophic factors that guide trigeminal nerve fibers into and throughout the DP. This process is tightly linked with dentin formation and mineralization. Our laboratory established a mouse model in which Tgfbr2 was conditionally deleted in DP mesenchyme using an Osterix promoter-driven Cre recombinase (Tgfbr2^cko). These mice survived postnatally with significant defects in bones and teeth, including reduced mineralization and short roots. Hematoxylin and eosin staining revealed reduced axon-like structures in the mutant mice. Reporter imaging demonstrated that Osterix-Cre activity within the tooth was active in the DP and derivatives, but not in neuronal afferents. Immunofluorescence staining for beta3 tubulin (neuronal marker) was performed on serial cryosections from control and mutant molars on postnatal days 7 and 24 (P7, P24). Confocal imaging and pixel quantification demonstrated reduced innervation in Tgfbr2^cko first molars at both stages compared to controls, indicating that signals necessary to promote neurite outgrowth were disrupted by Tgfbr2 deletion. We performed mRNA-Sequence (RNA-Seq) and gene onotology analyses using RNA from the DP of P7 control and mutant mice to investigate the pathways involved in Tgfbr2-mediated tooth development. These analyses identified downregulation of several mineralization-related and neuronal genes in the Tgfbr2^cko DP compared to controls. Select gene expression patterns were confirmed by quantitative real-time PCR and immunofluorescence imaging. Lastly, trigeminal neurons were co-cultured atop Transwell filters overlying primary Tgfbr2^f/f DP cells. Tgfbr2 in the DP was deleted via adenovirus-expressed Cre recombinase. Confocal imaging of axons through the filter pores showed increased axonal sprouting from neurons cultured with Tgfbr2-positive DP cells compared to neurons cultured alone. Axon sprouting was reduced when Tgfbr2 was knocked down in the DP cells. Immunofluorescence of dentin sialophosphoprotein in co-cultured DP cells confirmed reduced mineralization potential in cells with Tgfbr2 deletion. Both our proteomics and RNA-Seq analyses indicate that axonal guidance cues, particularly semaphorin signaling, were disrupted by Tgfbr2 deletion. Thus, Tgfbr2 in the DP mesenchyme appears to regulate differentiation and the cells’ ability to guide neurite outgrowth during tooth mineralization and innervation.